Setting Time of Alginate in Disinfectant Solutions: An In Vitro Study - Parajuli, Prakash Kumar; Pathak, Bibha (Journal of BP Koirala Institute of Health Sciences, 2024)
Background: While making impression, oral fluids like saliva, blood and other exudates that may contain pathogenic micro-organisms come in contact with impression materials and increase the risk of infection to dental practitioners, patients, and laboratory personnel. In order to prevent cross infection, all impressions should be thoroughly disinfected. The objective of this study was to investigate and compare the time taken by alginate to set when mixed with 1% povidone iodine and 0.1% chlorhexidine. Methods: In this in-vitro experimental study, a total of 69 samples were divided into three groups of 23 each based on the liquid used for mixing alginate. The liquid used were water, 1% povidone iodine and 0.1% chlorhexidine. The setting time was calculated following ADA specification no 18. Collected data were entered in Microsoft Excel 2016 and converted into Statistical Package for Social Science (SPSS) version 20.0 for statistical analysis. The data were analyzed using one way ANOVA and post hoc test. Results: The setting time of alginate was prolonged when 0.1% chlorhexidine and 1% povidone iodine were used as mixing liquid as compared to water. One way ANOVA and post-hoc Tukey test revealed statistically significant difference in setting time between all three groups (p < 0.001) Conclusion: The setting time was prolonged when 1% povidone iodine and 0.1% chlorhexidine are used to mix alginate powder. However, it may be clinically acceptable according to the established standards of ADA specification no 18 which allows a time up to 4.5 minutes for regular set impression materials.